The ABCs of Entering Indonesian Market: An International Community Service Program for Thailand’s SMEs - Ponziani, Regi Muzio; Danibrata, Aulia; Deitiana, Tita; Susanto, Yulius Kurnia; Firnanti, Friska; Purbasari, Niken; Prasetio, Arton Briyan (International Journal of Community Service & Engagement, 2025)
This community service initiative, conducted on October 17, 2024, at Thailand’s East Park Incubator, aimed to equip Thai SMEs (Small and Medium-Sized Enterprises) with strategies to enter the Indonesian market by addressing digitalization, cultural alignment, and regulatory compliance. Engaging 30 Thai SMEs, the program emphasized leveraging Indonesia’s digital ecosystem including platforms like Tokopedia, Shopee, Instagram, and TikTok to reach its young and huge population of over 212 million internet users, while highlighting demographic advantages such as a young workforce, halal product demand, and strategic geographic positioning. Key discussions covered cultural nuances like relationship-building practices, collective decision-making, and business etiquette to foster trust, alongside regulatory frameworks such as PT PMA requirements and tax policies. Participants demonstrated strong interest in Indonesia’s market potential, with plans or strategies to adopt localized digital marketing, partner with Indonesian businesses, and utilize e-commerce logistics. The initiative underscores the importance of academic-industry collaboration in facilitating cross-border SMEs expansion, fostering economic growth, and enhancing Thailand-Indonesia knowledge exchange through tailored market entry strategies.